Growth mechanisms and defect structures of B12As2 epilayers grown on 4 H-SiC substrates - Zhang, Yu; Chen, Hui; Dudley, Michael; Zhang, Yi; Edgar, James H.; Gong, Yinyan; Bakalova, Silvia; Kuball, Martin; Zhang, Lihua; Su, Dong; Zhu, Yimei (My University, 2012)
Epitaxial growth of icosahedral B12As2 on c-plane 4 H-SiC substrates has been analyzed. On on-axis c-plane 4 H-SiC substrates, Synchrotron white beam x-ray topography (SWBXT) revealed the presence of a homogenous solid solution of twin and matrix B12As2 epilayer domains. High resolution transmission electron microscopy (HRTEM) and scanning transmission electron microscopy (STEM) both revealed the presence of an ∼20 nm thick, disordered transition layer at the interface. (0003) twin boundaries are shown to possess fault vectors such as 1/3[1–100]B12As2, which originate from the mutual shift between the nucleation sites. On the contrary, B12As2 epilayers grown on c-plane 4 H-SiC substrates intentionally misoriented from (0001) towards [1–100] is shown to be free of rotational twinning. SWBXT, HRTEM and STEM all confirmed the single crystalline nature and much higher quality of the films. In addition, no intermediate layer between the epilayer and the substrate was observed. It is proposed that the vicinal steps formed by hydrogen etching on the off-axis 4 H-SiC substrate surface before deposition cause the film to adopt a single orientation during nucleation process. This work also demonstrates that c-plane 4 H-SiC with offcut toward [1–100] is potentially a good substrate choice for the growth of high-quality, single crystalline B12As2 epilayers for future device applications.
Keywords: Characterization; Defects; X-ray topography; Heteroepitaxy growth